English Law as Implicit Religion - Hanson, Sharon (Implicit Religion, 2007)
This article applies the concept of implicit religion to law in order to give a new understanding of English law: its sacredness and its theology; its organizational structures and its social forms. Having constructed a table of potential elements, illustrating the concept of implicit religion, read against both Christianity and Law, three entries from that table are explored in further detail. Ultimately, the article argues that not only is English law an implicit religion templated by Christianity, but that it contains within itself a sacred paradox, formed by the interaction of its implicit and explicit religious dimensions.